2018
DOI: 10.1038/s41467-018-04847-9
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized hippocampal oscillations underlie distinct aspects of human spatial memory and navigation

Abstract: The hippocampus plays a vital role in various aspects of cognition including both memory and spatial navigation. To understand electrophysiologically how the hippocampus supports these processes, we recorded intracranial electroencephalographic activity from 46 neurosurgical patients as they performed a spatial memory task. We measure signals from multiple brain regions, including both left and right hippocampi, and we use spectral analysis to identify oscillatory patterns related to memory encoding and naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
123
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 70 publications
(93 reference statements)
16
123
3
Order By: Relevance
“…Additionally, studies have demonstrated multiple sources of theta rhythms in the medial temporal lobe (Lega et al, 2012;Mormann et al, 2008), including a "low-theta" or delta band (1-4 Hz) in addition to the typical theta band (4-8 Hz). Based on observations of encoding-related increases in power (Burke et al, 2013;Lega et al, 2012;Miller et al, 2018) and PAC during verbal encoding are specific to the "low-theta" band (Lega et al, 2016), it has been proposed that lower frequency theta in humans reflects a homologue of rodent theta (Jacobs, 2014). In contrast to this body of work, we observed faster (i.e., predominantly greater than 4 Hz) memory-related theta dynamics.…”
Section: Discussioncontrasting
confidence: 69%
“…Additionally, studies have demonstrated multiple sources of theta rhythms in the medial temporal lobe (Lega et al, 2012;Mormann et al, 2008), including a "low-theta" or delta band (1-4 Hz) in addition to the typical theta band (4-8 Hz). Based on observations of encoding-related increases in power (Burke et al, 2013;Lega et al, 2012;Miller et al, 2018) and PAC during verbal encoding are specific to the "low-theta" band (Lega et al, 2016), it has been proposed that lower frequency theta in humans reflects a homologue of rodent theta (Jacobs, 2014). In contrast to this body of work, we observed faster (i.e., predominantly greater than 4 Hz) memory-related theta dynamics.…”
Section: Discussioncontrasting
confidence: 69%
“…In that regard, individuals with higher TBR are shown to exhibit larger declines of subjectively-experienced attentional control than those with lower TBR [26]. It is also reported that higher TBR is correlated with quick behavioral responses-to-choice stimuli, albeit with a high error rate [27]. …”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of such low theta waves in the left temporal lobe is reported to increase in amplitude when viewing familiar objects or locations [27]. The left temporal area of the brain is also thought to be the seat of episodic memory [28].…”
Section: Discussionmentioning
confidence: 99%
“…We developed AR and VR paradigms that adapted the "Treasure Hunt" spatial memory task, previously used in [17,18,20,31]. Treasure Hunt is an object-location associative memory task in which subjects are asked to remember the locations of various hidden objects in a virtual environment.…”
Section: Methodsmentioning
confidence: 99%
“…To compute this measure, we first calculated the raw distance for each target, which is the Euclidean distance between the coordinate of the location the subject selected for their response and the actual target object's coordinate. We then corrected this distance metric, which was important because different target locations can be biased to lead to different potential errors (e.g., if the target is in the center, the maximum error distance can be at most half of the diagonal, while for a target in the corner of the environment the maximum distance can be the full diagonal length of the environment, See Fig 3. For more information on this method see [20]). This correction also controls for potential differences in perceived size and scaling between virtual units in the virtual and augmented environment.…”
Section: Statisticsmentioning
confidence: 99%